2019
DOI: 10.1108/jsm-11-2018-0339
|View full text |Cite
|
Sign up to set email alerts
|

Design fiction diegetic prototyping: a research framework for visualizing service innovations

Abstract: Purpose The purpose of this paper is to present a design fiction diegetic prototyping methodology and research framework for investigating service innovations that reflect future uses of new and emerging technologies. Design/methodology/approach Drawing on speculative fiction, the authors propose a methodology that positions service innovations within a six-stage research development framework. The authors begin by reviewing and critiquing designerly approaches that have traditionally been associated with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 69 publications
0
3
0
1
Order By: Relevance
“…In addition to the acquisition of human needs and requirements, iterative design is also suitable for investigating “what-if” scenarios on design solutions. For instance, Kymäläinen et al ( 2017 ) and Harwood et al ( 2019 ) built fiction prototyping—video-illustrated and tangible interaction tools—to facilitate human-centred perception and cognition of the future potentials of products and/or services. This so-called design fiction—an interactive and tangible approach—evaluates alternative design solutions or criticizes existing ones (Knutz et al, 2014 ) before they are manufactured and/or delivered to customers, which enhances the robustness of iterative design by deeply understanding human experience.…”
Section: Literature Characterization Of Human-centred Design In Industry 40mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the acquisition of human needs and requirements, iterative design is also suitable for investigating “what-if” scenarios on design solutions. For instance, Kymäläinen et al ( 2017 ) and Harwood et al ( 2019 ) built fiction prototyping—video-illustrated and tangible interaction tools—to facilitate human-centred perception and cognition of the future potentials of products and/or services. This so-called design fiction—an interactive and tangible approach—evaluates alternative design solutions or criticizes existing ones (Knutz et al, 2014 ) before they are manufactured and/or delivered to customers, which enhances the robustness of iterative design by deeply understanding human experience.…”
Section: Literature Characterization Of Human-centred Design In Industry 40mentioning
confidence: 99%
“…In the last group of research interest, three studies present experience-driven approaches that visualize design scenarios (RR4) regarding future possibilities to exploit human experience. Based on design fiction, both Kymäläinen et al ( 2017 ) and Harwood et al ( 2019 ) demonstrated the usefulness of the video-illustrated prototype in avoiding the difficulty of interpreting abstract verbal descriptions of new design. This method enables designers to interactively envisage a spectrum of “what if” scenarios towards human experience that may then be explored by using the range of other design methods: focus groups, interviews, and questionnaires.…”
Section: Literature Characterization Of Human-centred Design In Industry 40mentioning
confidence: 99%
“…Ces processus de pensée complexe amènent l'apprenant à appréhender une situation concrète (Bonnardel, 2006). L'activité de conception mobilise la pensée prospective (apprendre à anticiper) qui permet de travailler dans une logique de scénarios (Harwood, Garry & Belk, 2020) et donc d'évaluer les possibles et d'à opérer les choix adaptés en regard des contraintes.…”
Section: Travailler La Collaboration à L'aide Du Designunclassified
“…[57] Thanks to design fiction, future possibilities could be explored [58] using "speculative design" methods that draw on creative practice [59]. In our research, the rationale for using design fiction is two-pronged: first, it has allowed us to generate debate among participants in the two workshops [60,61], second, design fiction is a very interesting and efficient way of developing prototypes that help participants to collectively project themselves in a speculative future [58,59]. In addition, Nägele et al [62] clearly demonstrate how design fiction constitutes a method and offers tools that are perfectly suited to users in vulnerable situations.…”
Section: Design Fictionmentioning
confidence: 99%